Structure, electronic structure, optical, and dehydrogenation catalytic study of (Zn1-zInz)(O1-xNx) solid solution - Mapa, Maitri; Sivaranjani, Kumarsrinivasan; Bhange, Deu S.; Saha, Biswajit; Chakraborty, Purushottam; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Chemistry of Materials, 2010)
Indium and nitrogen codoping in ZnO leads to a solid solution of InN in ZnO with I composition of(Zn1-zInz)(O1-xNx). A simple solution combustion method has been adopted to prepare the above materials in less than 10 min with metal nitrates as the metal loll source and urea as fuel. With reference to ZnO, significant increase in lattice parameters was observed with increasing In-content. However, the In2O3 phase was Observed along with InN for]it content >= 10%. Optical absorption extended into the Visible region, at least LIP to 550 nm, demonstrates an effective reduction of optical band gap due to the formation of solid Solution. A new feature observed just above O2p valence band in X-ray photoelectron spectroscopy (XPS) suggests the creation of N 2p states from InN; the N Is core level XPS result too confirms nitride contribution. Raman spectroscopy and secondary ion mass spectrometry results show direct In-N, Zn-N. and In-N-Zn fragments in (Zn1-zInz)(O1-x,N-x). Catalytic activity explored for Oxidation of 2-butanol to ethyl methyl ketone demonstrates a high selectivity at 350 and 400 degrees C. All of the above characteristics suggest the multifunctional nature of (Zn1-zInz)(O1-xNx) and its potential for other applications.